Faktor-Faktor yang Mempengaruhi Perilaku Konsumen dan Minat Beli Terhadap Keputusan Pembelian di Manna Kampus (Mirota Kampus) Jalan Menteri Supeno Pada Mahasiswa Yogyakarta - Albertina Deti Kurniati; Rinaldi Tanjung (CV. Aksara Global Akademia, 2026)
This study aims to examine the influence of consumer behavior and purchase intention on purchasing decisions at Manna Campus (Mirota Kampus), located on Menteri Supeno Street, among university students in Yogyakarta. A quantitative approach was employed in this research. The population comprised students who had previously purchased products at Manna Campus. A total of 150 respondents were selected through purposive sampling, with participants chosen according to predetermined criteria established by the researcher. Data were gathered using a questionnaire and processed with SPSS 2025. Prior to analysis, the research instrument underwent validity and reliability testing to ensure data quality. The data analysis techniques included descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination analysis, and hypothesis testing to evaluate the relationships among the variables.Based on the hypothesis testing results, Consumer Behavior was found to significantly influence Purchase Decisions, as reflected by a t-statistic of 6.196 and a significance value below 0.05. Likewise, Buying Interest showed a significant individual effect on Purchase Decisions, with a t-statistic of 6.282 and a significance level meeting the required criterion. The simultaneous analysis further demonstrated that the combination of Consumer Behavior and Buying Interest significantly contributes to Purchase Decisions, evidenced by an F-statistic of 183.191 and a p-value of 0.000. These findings support the acceptance of the alternative hypotheses and confirm the importance of both variables in shaping purchasing decisions.